Proposals for improved management in the South African state departement of forestry and especially in the eastern Transvaal region - Wilhelmij, H.(Horatius) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1964.